Reported Hydration Beliefs and Behaviors without Effect on Plasma Sodium in Endurance Athletes - Chlíbková, Daniela; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat; Bednář, Josef (Frontiers in Physiology, 2017)
Purpose: Little information is available on the association of hydration beliefs and behaviours in endurance athletes and exercise-associated hyponatremia (EAH). The aim of the present study was to determine hydration beliefs and behaviours in endurance athletes. Method: A hundred and thirty-eight recreational athletes [107 mountain bikers (MTBers) and 31 runners] competing in seven different endurance and ultra-endurance races completed pre- and post-race questionnaires, and a subgroup of 113 (82%) participants (82 MTBers and 31 runners) also provided their blood samples. Result: More than half of the participants had some pre-race (59%), mid-race (58%), and post-race (55%) drinking plan. However, participants simultaneously reported that temperature (66%), thirst (52%) and plan (37%) affected their drinking behaviour during the race. More experienced (years of active sport: p = 0.002; number of completed races: p < 0.026) and trained (p = 0.024) athletes with better race performance (p = 0.026) showed a more profound knowledge of EAH, nevertheless, this did not influence their planned hydration, reported fluid intake, or post-race plasma sodium. Thirteen (12%) hyponatremic participants did not differ in their hydration beliefs, race behaviours, or reported fluid intake from those without post-race EAH. Compared to MTBers, runners more often reported knowledge of the volumes of drinks offered at fluid stations (p < 0.001) and information on how much to drink pre-race (p < 0.001), yet this was not associated with having a drinking plan (p ˃ 0.05). MTBers with hydration information planned more than other MTBers (p = 0.004). In comparison with runners, more MTBers reported riding with their own fluids (p < 0.001) and planning to drink at fluid stations (p = 0.003). On the whole, hydration information was positively associated with hydration planning (n = 138) (p = 0.003); nevertheless, the actual reported fluid intake did not differ between the group with and without hydration information, or with and without a pre-race drinking plan (p ˃ 0.05). Conclusion: In summary, hydration beliefs and behaviours in the endurance athletes do not appear to affect the development of asymptomatic EAH.